Lamella-nanostructured eutectic zinc–aluminum alloys as reversible and dendrite-free anodes for aqueous rechargeable batteries - Wang, Sheng-Bo; Ran, Qing; Yao, Rui-Qi; Shi, Hang; Wen, Zi; Zhao, Ming; Lang, Xing-You; Jiang, Qing (Nature communications, 2020)
Metallic zinc is an attractive anode material for aqueous rechargeable batteries because of its high theoretical capacity and low cost. However, state-of-the-art zinc anodes suffer from low coulombic efficiency and severe dendrite growth during stripping/plating processes, hampering their practical applications. Here we show that eutectic-composition alloying of zinc and aluminum as an effective strategy substantially tackles these irreversibility issues by making use of their lamellar structure, composed of alternating zinc and aluminum nanolamellas. The lamellar nanostructure not only promotes zinc stripping from precursor eutectic Zn 88 Al 12 (at%) alloys, but produces core/shell aluminum/aluminum sesquioxide interlamellar nanopatterns in situ to in turn guide subsequent growth of zinc, enabling dendrite-free zinc stripping/plating for more than 2000 h in oxygen-absent aqueous electrolyte. These outstanding electrochemical properties enlist zinc-ion batteries constructed with Zn 88 Al 12 alloy anode and K x MnO 2 cathode to deliver high-density energy at high levels of electrical power and retain 100% capacity after 200 hours. Aqueous rechargeable Zn-ion batteries are attractive energy storage devices, but their wide adoption is impeded by the irreversible metallic Zn anode. Here the authors report lamellar-nanostructured eutectic Zn/Al alloys as reversible and dendrite-free anodes for improved battery performance.